IMPLEMENTATION OF DATA MINING WITH NAVE BAYES CLASSIFIER TO SUPPORT THE MARKETING STRATEGY OF THE MARKETING SECTION AT PT. MEGA PANCA JAYA BUMI - Wahyudi, Ricki; Ramadhani, Putri Saumi; Utomo, Ardy Budi; Anita, Anita (INFOKUM, 2022)
In the business world, competition is something that is already familiar to business actors. The bigger the business can compete, the bigger the challenges faced by business actors. One of them is a company in residential property owned by PT. Mega Panca Jaya Bumi. The newly developing company should have thought of strategies in marketing its business. In order to avoid a decrease in interest and profits, it is only natural that these new strategies can be implemented in data processing techniques or Data Mining which is expected to increase marketing and the number of markets is wider. The data processing in this study uses the Naïve Bayes Classifier Algorithm in its calculations. Data taken from the company as many as 300 records from 2019 to 2021. In this study, the process of the data experiment was carried out by applying the Python programming language version 3.8 technology. The results of testing the data got an accuracy rate of 56%